Persepsi Petani Perkotaan terhadap Aktivitas Sistem Subak (Kasus di Subak Anggabaya Desa Penatih Kecamatan Denpasar Timur Kota Denpasar) - PRADIPTA, I PUTU SABDA; PUTRA, I GEDE SETIAWAN ADI; SUDARTA, WAYAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.1, Januari 2016, 2016)
Abstract The Urban Farmer’s Perception to Subak System Activity (The Case of Anggabaya Subak of Penatih Village East Denpasar Sub-District Denpasar City) Farmer’s mind set is an important thing to the existence of subak system agriculture in urban area.  According to the problem above, this research has purpose to find out the perception of urban farmer to subak system activity at Anggaya Subak of Penatih Village East Denpasar Sub-district Denpasar City.  Determining of research location used the purposive method.  Result of research showed that the urban farmer’s perception to subak system activity at Anggaya Subak of Penatih Village East Denpasar Sub-district Denpasar City is including in the good category (77.15%).  This data shows that the farmer has positive mind set to the preservation of agriculture work of subak system.  It is strengthen by the result achieved by its three supporting aspects, including mind set aspect which is including in the good category (83.83%), social system aspect which is including in the good category (83.78%) and the artifact aspect which is including in fair category (64.78%).  Based on the research result, to support the farmer’s business activity it is expected that the farmers are not only based their activity to dewasa ayu but they should also communicate to the related institution Keywords : perception, urban farmers, agriculture of subak system.